Orphan Toxin OrtT (YdcX) of Escherichia coli Reduces Growth during the Stringent Response - Sabina Islam; Michael J. Benedik; Thomas K. Wood (Toxins, 2015)
Toxin/antitoxin (TA) systems are nearly universal in prokaryotes; toxins are paired with antitoxins which inactivate them until the toxins are utilized. Here we explore whether toxins may function alone; i.e., whether a toxin which lacks a corresponding antitoxin (orphan toxin) is physiologically relevant. By focusing on a homologous protein of the membrane-damaging toxin GhoT of the Escherichia coli GhoT/GhoS type V TA system, we found that YdcX (renamed OrtT for orphan toxin related to tetrahydrofolate) is toxic but is not part of TA pair. OrtT is not inactivated by neighboring YdcY (which is demonstrated to be a protein), nor is it inactivated by antitoxin GhoS. Also, OrtT is not inactivated by small RNA upstream or downstream of ortT. Moreover, screening a genomic library did not identify an antitoxin partner for OrtT. OrtT is a protein and its toxicity stems from membrane damage as evidenced by transmission electron microscopy and cell lysis. Furthermore, OrtT reduces cell growth and metabolism in the presence of both antimicrobials trimethoprim and sulfamethoxazole; these antimicrobials induce the stringent response by inhibiting tetrahydrofolate synthesis. Therefore, we demonstrate that OrtT acts as an independent toxin to reduce growth during stress related to amino acid and DNA synthesis.